2017
DOI: 10.1371/journal.pone.0176545
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of uridine production of Bacillus subtilis by atmospheric and room temperature plasma mutagenesis and high-throughput screening

Abstract: In the present study, a novel breeding strategy of atmospheric and room temperature plasma (ARTP) mutagenesis was used to improve the uridine production of engineered Bacillus subtilis TD12np. A high-throughput screening method was established using both resistant plates and 96-well microplates to select the ideal mutants with diverse phenotypes. Mutant F126 accumulated 5.7 and 30.3 g/L uridine after 30 h in shake-flask and 48 h in fed-batch fermentation, respectively, which represented a 4.4- and 8.7-fold inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…More and more experimental results have also showed that the ARTP as a new kind of physical mutation tool has a bright prospect for the genome mutation of the organisms with rapid mutation, high diversity of mutants and high safety 1,4 . Up to now, ARTP as a novel powerful mutagenesis method has been successfully used to mutation breeding of more than 110 kinds of microorganisms and plants as well animals [19][20][21][22]25 . Generally, mutagenesis of organisms is a complex process, dependent on the cellular DNA damage strength and the subsequent repair system of damaged DNA, which allows mutation to occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More and more experimental results have also showed that the ARTP as a new kind of physical mutation tool has a bright prospect for the genome mutation of the organisms with rapid mutation, high diversity of mutants and high safety 1,4 . Up to now, ARTP as a novel powerful mutagenesis method has been successfully used to mutation breeding of more than 110 kinds of microorganisms and plants as well animals [19][20][21][22]25 . Generally, mutagenesis of organisms is a complex process, dependent on the cellular DNA damage strength and the subsequent repair system of damaged DNA, which allows mutation to occur.…”
Section: Discussionmentioning
confidence: 99%
“…1). We have employed this system to mutate the genomes of various microbes and plants as well as animals, including bacteria, microalgae, fungi, and yeast 1,4,[19][20][21][22][23][24] . The results of those studies indicated that ARTP mutation is a rapid, effective, convenient, and multifaceted means of generating mutant libraries with sufficient diversity for the improvement of phenotypes.…”
mentioning
confidence: 99%
“…This incurs DNA damage which is subsequently repaired by the SOS ("Save Our Soul") system leading to DNA alterations [8,9]. ARTP technology generates high mutation frequencies, is simple and safe, and is widely used for bacteria [10][11][12][13], fungi [14,15], and microalgae [16][17][18]. On the other hand, mutations in strains due to streptomycin resistance are closely related to their ability to produce antibiotics [19].…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric and room temperature plasma (ARTP) mutagenesis can induce breakage in plasmid DNA and oligonucleotides through treatment with a diverse range of plasma doses . Compared to conventional mutation methods, ARTP mutagenesis provides highly homogeneous plasma jets under mild conditions, induces mutations at a higher rate, and is environmentally friendly, efficient, and easy to operate. Recently, this method has been applied on multiple microorganisms to obtain targeted phenotypes. , Fan et al treated Bacillus subtilis with ARTP and obtained a high uridine-producing strain, in which production was 8.7-fold higher than the parent strain . This technology has also been applied on yeast.…”
mentioning
confidence: 99%
“…18,19 Fan et al treated Bacillus subtilis with ARTP and obtained a high uridine-producing strain, in which production was 8.7-fold higher than the parent strain. 20 This technology has also been applied on yeast. Luo et al used this mutagenesis method along with a screening strategy to screen pyruvate-producing Candida glabrata mutant strains and obtained 35.4% higher titer than that obtained from the wild-type strain.…”
mentioning
confidence: 99%